Relationship between MTHFR C677T, homocysteine, and ischemic stroke in a large sample of the Han Chinese population. Issue 38 (23rd September 2022) - Jin, Ming; Wang, Ningning; Li, Xueyan; Zhang, Hao; Zhou, Jexin; Cong, Mingyu; Niu, Jun; Lin, Chongyang; Hu, Ying; Wu, Nan; Liu, Jicheng; Zhang, Keyong; et al.
Abstract : Ischemic stroke, one of the prevalent causes of death and disability worldwide, is linked to environmental and genetic factors, including polymorphisms in the methylenetetrahydrofolate reductase ( MTHFR ) gene involved in homocysteine metabolism. The present study aimed to explore the relationship between the MTHFR C677T variant, plasma homocysteine, and risk of developing large-artery atherosclerotic ischemic stroke (LAAIS) among Han Chinese. A population-based case-control study, which included 1810 patients with LAAIS and 1765 unrelated control subjects, was conducted. Compared to the controls, LAAIS patients had a significantly higher prevalence of hypertension, diabetes mellitus, smoking, and alcohol consumption ( P < .001), as well as significantly higher mean fasting blood glucose, triglyceride, total cholesterol, and plasma homocysteine levels ( P < .001). The TT homozygous genotype correlated with increased risk of developing LAAIS, as indicated by a significantly higher odds ratio (OR) compared to the CT and CC genotypes, in both additive (OR = 3.215, P = .01) and recessive models (OR = 3.265, P = .01). The plasma homocysteine level was genotype-dependent according to the following trend: TT > CT > CC. In conclusion, our data demonstrate that, in spite of its low prevalence in both patients and controls (1.5% vs 0.8%), the MTHFR C677T variant could, at least in part, affect homocysteine levels and this, either alone or in combination with other factors, increases the risk of LAAIS.